Analysis of blood gas composition indicators in premature babies with neonatal sepsis - Vlasova, Olena; Kolyubakina, Larysa (ScienceRise: Medical Science, 2020)
The aim of the study was analysis of oxygen status of patients with neonatal sepsis during monitoring of premature infants. Materials and methods. Indicators of oxygen status of capillary blood were assessed in premature infants with neonatal sepsis who were treated at the Regional Perinatal Center in Khmelnytsky during 2017–2018. The study included mostly deeply premature babies, including those with extremely low weight. A full range of clinical and laboratory studies, including determination of oxygen status of capillary blood. Research results. Our results allow us to conclude that while such indicators as pH, pO2, BEb3, % SO2 do not change significantly, the trouble can be detected using indicators such as AdDO2, RI, PI, which reflect the state of oxygenation with impaired ventilation. -perfusion ratios, increased blood shunting and the processes of delivery and consumption of oxygen at the tissue level. The calculated indicator "PIP×FiO2" was less sensitive to assess changes in the lungs and did not correspond to the clinical picture of the severity of the patient's condition. Conclusion. Thus, the determination of AdDO2, RI, PI capillary blood can be used as informative indicators for determining the oxygen status in premature infants, which is of significant practical importance in terms of limited monitoring of the gas composition of arterial blood